Dependence of Co/Fe ratios in Co-Fe layered double hydroxides on the structure and capacitive properties. (20th April 2016) - Ma, KeYuan; Cheng, J.P.; Zhang, Jing; Li, Min; Liu, Fu; Zhang, XiaoBin
Graphical abstract: The incorporation of Fe 2+ /Fe 3+ not only prevents the formation of β-Co(OH)2 but also delivers a higher capacitance even at a high Fe content. However, too high Fe content may destroy the layered structure of LDHs and lead to the decay of the electrochemical performances. Abstract: Co-Fe layered double hydroxides (LDHs) with different Co/(Fe 2+, Fe 3+ ) atomic ratios are fabricated via co-precipitation followed by an I2 partial oxidation process. The initial Co/Fe ratio in solution is changed in a wide range and has a significant influence on the phase and structure of the product. Structural analysis confirms that Co-Fe LDHs with four Co/Fe molar ratios (2.35, 1.07, 0.58 and 0.24) shows a typical hydrotalcite-like structure and layered plate-like morphology. A high Fe content will destroy the hydrotalcite structure and lead to the formation of magnetite particles. Electrochemical data demonstrate that the specific capacitance of Co-Fe LDHs is strongly dependent on Co/Fe ratio. The Co-Fe LDHs with a high Co/Fe ratio of 2.35 can deliver the highest capacitance of 728 F g −1 at 1 A g −1 among them and when assembled into asymmetric supercapacitor with activate carbon as negative material, it can exhibit an energy density of 27.3 Wh kg −1 at a power density of 823.5 W kg −1 . The incorporation of Fe not only prevents the formation of β-Co(OH)2 but also delivers a high capacitance. But, too much Fe is not preferred because it will lead to unstable structures and poor electrochemical performance due to the generation of iron compounds.